Vertical distribution of birds in a temperate forest with different perturbation levels - Ugalde-Lezama, Saúl; Valdez-Hernández, Juan Ignacio; Ramírez-Valverde, Gustavo; Alcántara-Carbajal, José Luis; Velázquez-Mendoza, Juan (Instituto de Ecología, A.C., 2016)
In the period from February through June 2004, the presence of different bird species was studied in two zones located at the Experimental Forest Station Zoquiapan (EFEZ for its Spanish acronym), state of Mexico, one with slightly disturbed pine forest (ZOQ 1) and another with mixed perturbed forest (ZOQ 2). The points recounting method with fixed radio for bird monitoring was used as well as the square embedded method and the quadrant with a central point, the last one to allow sampling the vegetation. The distribution of birds in vertical vegetation strata was characterized and compared using Poisson regression analysis and frequency observation; furthermore, a specific analysis was developed to describe the vegetal structure in both zones. The vertical distribution of birds followed four patterns: low (B), high (A), high-low (AB) and indeterminate (I). The individual’s abundance per stratum had a different value within strata and zones; in both sites the upper stratum showed a greater abundance than in the low and medium ones, although the number of individuals per specie registered in each stratum was the greatest in the perturbed mixed forest. The relative importance value (VIR for its Spanish acronym) of vegetation confirmed than ZOQ 1 had Pinus hartwegii as the predominant specie with some shrubs of Penstemon gentianoides and Senecio asteracae. ZOQ 2 was a mixed forest comprised by S. asteracae, P. gentianoides, Lupinus montanus shrubs and Alnus jorullensis, P. hartwegii and Abies religiosa trees. The height histograms determined two and three vertical strata, respectively.